The customer commitment towards debt payment in Malaysia banking sector / Mohammad Haziq Rahmat - Rahmat, Mohammad Haziq (2012)
This study aims to examine the Customer Commitment towards Debt Payment in Malaysia Banking Sector with comprehensive review in default payment on financing. This study has been done to know the relationship between four independent variables which are locality, service quality, living cost and situational factor with the dependent variables which is default payment on financing. The study based on 277 respondents’ in Kuala Lumpur area which are the customers’ of Malaysia banking sector. The finding shows that only locality and living cost are significantly and positively contributed to the default payment on financing. Meanwhile, the other two independent variables are not significantly related with dependent variable. The finding also proved that the four independent variables chose, have weak influence towards dependent variable. Most of the dependent variable in the finding is influenced by the other variables.